Harmful Effect of Beer on Bovine Enamel Microhardness - In Vitro Study. - Rayssa Ferreira Zanatta; Maria Ângela Lacerda Rangel Esper; Marcia Carneiro Valera; Renata Marques Melo; Eduardo Bresciani (PLoS ONE, 2016)
This study aimed to evaluate the effect of beers on the bovine enamel microhardness. Fifty rectangular (1 x 3 x 1 mm-height x width x thickness) enamel specimens were obtained from permanent bovine incisors, and divided into five groups (n = 10) according to the treatment employed: Saliva, Coke, Brahma, Heineken, and Budweiser. Microhardness (Knoop) were obtained before; after 5, 30 and 60 min of immersion in each solution. The data were analyzed using repeated two-way ANOVA and Tukey´s test (p<0.05). Coke decreased the microhardness in all immersion times, and Heineken, showed low values after 60 minutes. Beers tested have low potential to cause enamel erosion when compared to Coke.